Arkansas Settler: Minari and Movies About Immigrants to the Heartland. (3rd July 2021) - Beck, Bernard
Abstract : A recent award-winning movie, Minari, can be contrasted with other recent movies that focus on grief, rage and disappointment about America's troubles, injustices, inequalities and cruelties. Minari is about a Korean immigrant family in America trying to make a life by farming in rural Arkansas in the 1980s. The context of similar, though not identical, movies about Americans facing insuperable odds to pursue the American Dream is commonplace in today's cinema. The dream has made stories about successful struggles a fundamental theme in movies and serves to reinforce sentiments that validate the American Experiment.